Green Synthesized Nanoceria Applied as a Fenton-Like Catalyst for Degrading Methylene Blue - Dilek Özyurt; Fatoş Ayça Özdemir Olgun; Birsen Demirata Öztürk; Mustafa Reşat Apak (Aquatic Sciences and Engineering)
Nanomaterials are preferred for scientific studies due to their spectral properties and perfect surface appearance. This study aims to introduce a novel, environmentally friendly, photocatalytic method for degrading methylene blue (MB) in aqueous solutions. With this purpose in mind, the study synthesizes nanoceria particles and coats them with zahter (Thymbra spicata; zahter-coated nanoceria, ZCNC) following the main outlines of green chemistry as characterized by SEM and FTIR analyses. The study proposes this new nanoparticle (with the aid of H2 O2 and UV combinations) as an alternative to iron in Fenton-type reactions for enabling MB degradation. The maximum efficiency was observed through the ternary combination of zahter-coated nanoceria, UV light, and H2 O2 at 63% concentration. The degradation of the MB solution was achieved by installing a small amount of ZCNC (0.1g), after which the absorbance values were measured at 664 nm. According to the possible reaction kinetics discussed within the study, the reaction rate was calculated at 1.49 × 10-2 min -1, thus enabling a faster reaction for a better evaluation of the reaction mechanism compared to other degradation processes that have been previously investigated.